1991
DOI: 10.1017/s095977430000024x
|View full text |Cite
|
Sign up to set email alerts
|

The Taï Plaque and Calendrical Notation in the Upper Palaeolithic

Abstract: Analysis of the Taï plaque, the most complex Upper Palaeolithic composition, has revealed evidence of the problem-solving and visual cueing strategies involved in the accumulation of the marks. The composition consists of a boustrophedon sequence of short horizontal containing lines or sections, each of which carries irregular subsets of marks. The analysis proceeded in stages over a period of twenty years, initially with use of a microscope, but did not involve cross-sectional analysis or counting. The theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 5 publications
0
34
0
1
Order By: Relevance
“… An engraved bone plaque (8.8 cm) from Grotte du Tai, France, ca. 12,000 years old (after Marshack) . Use of marks as tallies not only frees working memory capacity for additional executive tasks, but acts as a material scaffold for the development of a true number concept …”
Section: Insight 4: a Final Enhancement Of Executive Reasoning Abilitmentioning
confidence: 99%
See 1 more Smart Citation
“… An engraved bone plaque (8.8 cm) from Grotte du Tai, France, ca. 12,000 years old (after Marshack) . Use of marks as tallies not only frees working memory capacity for additional executive tasks, but acts as a material scaffold for the development of a true number concept …”
Section: Insight 4: a Final Enhancement Of Executive Reasoning Abilitmentioning
confidence: 99%
“…Homo erectus, as compared to apes, demonstrated enhanced executive reasoning; late Pleistocene hominins, as compared to Homo erectus, demonstrated enhanced abilities. At some time after the initial appearance of anatomically 88 Use of marks as tallies not only frees working memory capacity for additional executive tasks, but acts as a material scaffold for the development of a true number concept. 84 modern humans in the South African Middle Stone Age, two provocative types of executive reasoning made an appearance.…”
Section: Insight 4: a Final Enhancement Of Executive Reasoning Abilitmentioning
confidence: 99%
“…Cases in point for the Lower Palaeolithic are the sequentially notched long bone shaft fragments from the Lower Pleistocene site of Kozarnika (Guadelli and Guadelli, 2004) and a mammoth shaft fragment from Bilzingsleben which exhibits a 'fanlike' engraved motif (Mania and Mania, 1988;Behm-Blancke, 1983;Steguweit, 1999). Among the objects found at Mousterian sites, the Tata nummulite which has a cross formed by a line perpendicularly crossing a natural crack (Vértes, 1964;Marshack, 1976), sequential incisions from Suard (Crémades, 1996), Saint Anne I (Raynal and Seguy, 1986), Vaufrey (Vicent, 1988), Oldisleben 1 (Günther, 1994), Le Moustier (Peyrony, 1930), Lartet (Debénath and Duport, 1971), Marillac (Duport, 1973), Le Petit Puymoyen, (Debénath and Duport, 1971), La Quina (Martin, 1910;Marshack, 1991), Cotencher (Dubois and Stehlin, 1933), La Ferrassie (Capitán and Peyrony, 1912;Bordes, 1969), L'Ermitage (Pradel and Pradel, 1954), Tagliente (Leonardi, 1988), Turské Mastale (Neustupny, 1948), Temnata (Crémades et al, 1995), Prolom II (Stepanchuk, 1993), Axlor (Barandiarán and García-Diez, 2007) and Vergisson IV (d' Errico et al, 2003;Soressi and d'Errico, 2007;Vandermeersch et al, 2008) are noteworthy. The only known examples from the Near East comprise a cortex of a flint flake engraved with a set of concentric lines from Quneitra (Goren-Inbar, 1990;Marshack, 1996;d'Errico et al, 2003) in a level dated to ca.…”
Section: Early Engravingsmentioning
confidence: 99%
“…While few comparable markings are signaled at other Middle Palaeolithic sites (d' Errico and Villa, 1997;d'Errico et al, 2003) they are abundant in Upper Paleolithic contexts (Marshack, 1964;; but see also Knight , 1995). It has been suggested that these types of objects were used to record the passage of time or to more generally store information outside the body (Marshack, 1964(Marshack, , 1991Robinson, 1992;d'Errico, 1995) and their discovery at a European Middle Paleolithic site would be of great significance. What is unusual about the Molodova bones is that not only are the lines on these ribs evenly spaced but they are, in fact, perfectly equidistant.…”
Section: Was There Symboling At Molodova I During the Mp?mentioning
confidence: 99%
“…These types of studies include projects that are oriented toward understanding techniques of manufacture (e.g., White, 2001White, , 2006Henshilwood, 2004;d'Errico et al, 2005) including the chronological ordering of marks in notation systems (e.g., Marshack, 1991;d'Errico, 1995 and those that are concerned with discerning anthropogenic from naturally produced "art objects" (e.g. d 'Errico and Nowell, 2000).…”
mentioning
confidence: 99%